Watson’s Error Category: Analysis of Student Errors in Solving Algebraic Calculation Operation Problems - Nurhidayah, Dwi Avita; Ikmawati, Egidia; Wahyudi, Wahyudi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
Algebra material is the initial material in mathematics learning for junior high school students, which is a transfer from real material to abstract material, especially for the material for algebraic arithmetic operations is the basic material that students must master before studying higher-level algebraic material. This research is motivated by the presence of several students who still make mistakes in solving algebraic arithmetic operations. Therefore, this research aims to describe the forms of errors made by students in solving algebraic arithmetic operations based on Watson's error category. This research is a qualitative descriptive study. The subject of this research is 4 students of class VII A of MTs Muhammadiyah 2 Jenangan. Data collection techniques were conducted by giving written tests and interviews. The instruments used in this research were test questions and interview guidelines. Research subjects were selected based on the test results of students who made the most mistakes according to Watson's error category, and have good communication skills based on teacher recommendations. Data analysis was conducted with the stages of data reduction, data presentation, and data verification or concluding. The research results show that in solving algebraic arithmetic operations, the students made an error based on Watson's error category, including inappropriate data, inappropriate procedure, omitted data, omitted conclusion, response level conflict, and skill hierarchy problem. Besides the errors made by students, there were errors according to Watson's error category that were not made by students, namely undirected manipulation and other